Kajian Literatur Disposisi Matematis dengan Model PBL Berbantuan Software Materi Perbandingan SMP - Richa Aulya; Sischa Ilma Nafia; Savitri Wanabuliandari (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
This study has the objective to analyze the literature review regarding the disposition mathematical model of Problem Based Learning (PBL) aided software-based instructional media is media Articulate Storyline on comparative material for learners junior high school (SMP). Disposition of mathematical ability is very important to be improved, it is done in an effort to minimize the low active learners junior high school. The method used in this study is a qualitative method approach literature review and study of literature. Reference this research comes from national journal articles within the last 5 years (2017-2022). From some reference data obtained, the results showed that of the 10 national journal articles obtained have as many as six articles that correspond systematically based on the topic title of this research. Application of PBL models and media software Articulate Storyline in secondary schools in mathematics learning process material is appropriate comparison to the upgrading of mathematical disposition that is used as a reference. Application of PBL models and media software Articulate Storyline in secondary schools in mathematics learning material comparisons can improve and develop mathematical disposition affective abilities possessed by every learner.